Clear Filters
Clear Filters

How to solve a complicated equation?

5 views (last 30 days)
There is a Equation G. How to obtain the values of α and β when G=0?
G=-(-Omega^3*tau + (alpha + beta)*Omega)^2 - (Omega^2 - alpha*f)^2.
The answer:
alpha = Omega^2*cos(Omega*tau)/f;
beta = Omega*(f*sin(Omega*tau) - Omega*cos(Omega*tau))/f.
CAN anyone help me with this issue??? Thanks!!!
Cola on 16 Jul 2021
@Star Strider I obtain the values, and thank you very much for the help!!!
syms Omega tau alpha beta f
[ A, B ] = solve( [ -Omega^3*tau + (alpha + beta)*Omega == 0, Omega^2 - alpha*f == 0 ], [ alpha, beta ] )

Sign in to comment.

Accepted Answer

David Goodmanson
David Goodmanson on 16 Jul 2021
Edited: David Goodmanson on 16 Jul 2021
Hi Cola,
Since there is one equation and two unknowns, it must be possible to define, say, beta in terms of alpha, where alpha can be anything. For G = 0 we have
(-Om^3*t + (a+b)*Om)^2 = -(Om^2 - a*f)^2
-Om^3*t + (a+b)*Om = +-*i*(Om^2 - a*f)
where there are obvious notational substitutions for Omega, tau, alpha, beta, and the +- choice gives two different solutions. Solving for b,
b = (1/Om)*( Om^3*t -a*Om +-i*(Om^2 - a*f) )
where 'a' can be anything. Solving instead for a (this does not give a different family of solutions, rather the same ones expressed differently) gives
a = (Om^3*t +-i*Om^2 -b*Om)/(Om +-i*f)
Here the sign in the denominator (+ or -) has to match the sign in the denominator, and b can be anything. The choice b = 0 gives the solutions from Star Strider.
  1 Comment
Cola on 16 Jul 2021
I really thank you and sincerely wish you all the best.

Sign in to comment.

More Answers (0)


Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!